Hemorrhoidal artery ligation with Doppler guidance vs digital guidance for grade II-III hemorrhoidal disease treatment: Study protocol clinical trial (SPIRIT Compliant). Issue 15 (April 2020) - Markaryan, Daniil; Tulina, Inna; Garmanova, Tatiana; Bredikhin, Mikhail; Alikperzade, Aftandil; Tsarkov, Petr
Abstract: Introduction: Hemorrhoidal artery ligation (HAL) with Doppler guidance and suture fixation of hemorrhoidal nodes (RAR) is a popular minimally invasive technique for hemorrhoidal disease (HD) treatment which uses an ultrasound probe to detect hemorrhoidal arteries for further ligation. We hypothesized that ultrasound guidance has no advantages over manual hemorrhoidal arteries detection for HD treatment. The aim is to compare the results of HAL-RAR procedure in patients with stage II-III HD with Doppler and manual HA detection. In this ongoing randomized, controlled, single center clinical study 204 patients randomly divides into group A (HAL-RAR with Doppler US navigation) and group B (HAL with manual HA detection and mucopexy) are planned to be included. The primary endpoint was recurrence of any symptoms of HD; secondary endpoints were pain syndrome severity, treatment satisfaction (1 to 5 points), and need for the drug therapy in 30 days and 8 weeks after surgery. Conclusion: Ultrasound guidance technology of HAL with mucopexy could have the same efficacy the manual HA detection regarding the HD treatment effectiveness and patient satisfaction. Abstract : Supplemental Digital Content is available in the text